Multilayer Neural Network Approach in Heart Disease Prediction: Investigating a Framework - Nurulhikmah Syed Yasin, Sharifah; Syahira Sabrina Ab Rahman, Lily; Nadia Hassan, Nursyafiqah; Adilin Mohd Abd Majid, Hayati; Raju, Rajeswari; Nordin, Rosmawati (International Journal of Engineering and Technology, 2018)
The early detection of heart disease is vital to avoid sudden death. There are several symptoms that are familiar to heart disease patients. By analyzing the symptoms and assist with ECG signal's pattern, doctors would be able to confirm the heart disease. Since the conventional method of heart disease detection is quite tedious, the automatic detection is proposed. To automate the early detection, a number of adequate algorithms have been proposed in many studies. The algorithms receive input of patientsâ€™ details and generate the predicted result. Therefore, this study is proposed to implement and investigate the performance of multilayer neural network (MNN) approach in producing the heart disease prediction.Â Â